A polytetrafluoroethylene composite material for medical packaging and preparation method thereof
By introducing modified cellulose base polymer, silicon/sodium silicate composite material, modified nano metal oxides and polyethylene pyrigne, the pose -of -ethyl ethylene mechanical performance has been solved, and the lack of antibacterial properties is solved. The problem is to achieve the high toughness, hardness and antibacterial and antibacterial and antibacterial effects of the material, which is suitable for the field of pharmaceutical packaging.
Patent Information
- Application Number
- CN202411397623.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The application of polytetrafluoroethylene in the field of pharmaceutical packaging is limited by its poor mechanical properties and lack of obvious antibacterial properties.
Polytetrafluoroethylene is modified by introducing modified cellulose-based polymers, silica/sodium silicate composites, modified nanometal oxides and polyvinylpyrrolidone to improve its toughness, hardness and antibacterial and bacteriostatic effects.
It significantly improves the toughness and hardness of polytetrafluoroethylene composite materials, gives the material antibacterial bacteriostatic effect, and enhances its performance stability and processing adaptability in the field of pharmaceutical packaging.
Smart Images

Figure CN118910754B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a polytetrafluoroethylene composite material for medicine packaging and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene is an engineering plastic with excellent performance. It is polymerized from the monomer tetrafluoroethylene. The carbon chain of polytetrafluoroethylene is protected by fluorine atoms to form a spiral structure. The bond energy of the carbon-fluorine bond is very high and not easy to break, which makes polytetrafluoroethylene have excellent chemical stability, corrosion resistance and high temperature resistance. It has a wide range of applications in the field of pharmaceutical packaging. Especially when making containers such as glass bottle caps and gaskets, polytetrafluoroethylene can not only prevent chemical contamination, but also ensure the purity of drugs. In addition, polytetrafluoroethylene also has the characteristics of biological inertness, extremely low surface energy and excellent electrical insulation properties, making it widely favored in medical devices, pharmaceutical containers, packaging films, etc. However, due to the poor mechanical properties of polytetrafluoroethylene and its lack of obvious antibacterial properties, its further application in the field of pharmaceutical packaging has been restricted.
[0003] The Chinese patent with the authorization announcement number CN101775186B uses polytetrafluoroethylene and one or more of molybdenum disulfide, aluminum oxide, copper powder, graphite, silicon dioxide or stainless steel powder to prepare a polytetrafluoroethylene composite material, which significantly improves the wear resistance of the material, but the polytetrafluoroethylene composite material provided by this technology has a limited application range and cannot meet the needs of medical packaging. The Chinese patent with the publication number CN102924854A uses polytetrafluoroethylene and high stereopolymer polyacrylonitrile to prepare a polytetrafluoroethylene composite material, solving the problem of poor wear resistance and low compatibility of polytetrafluoroethylene resulting in poor performance of the mechanism. However, the steps designed in the preparation process such as low-temperature freezing and gamma-ray irradiation increase the complexity of processing and increase production costs. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a polytetrafluoroethylene composite material for pharmaceutical packaging and a preparation method thereof. The present invention modifies polytetrafluoroethylene by introducing modified cellulose-based polymers, silicon dioxide / sodium silicate composite materials, modified nano metal oxides and polyvinyl pyrrolidone: the modified nano metal oxides and the modified cellulose-based polymers work synergistically to improve the toughness and hardness of the polytetrafluoroethylene composite material while giving the material a certain antibacterial and antibacterial effect, thereby helping to protect the safety of pharmaceutical products; the introduced silicon dioxide / sodium silicate composite material can enhance the wear resistance and heat resistance of polytetrafluoroethylene and improve its performance stability in harsh environments; at the same time, the combination of polyvinyl pyrrolidone and cellulose-based polymers can significantly improve the processing performance of polytetrafluoroethylene, enhance its molding fluidity and processing adaptability, and facilitate subsequent processing.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a polytetrafluoroethylene composite material, wherein the polytetrafluoroethylene composite material comprises polytetrafluoroethylene, a modified cellulose-based polymer, a silicon dioxide / sodium silicate composite material, a modified nano metal oxide and polyvinyl pyrrolidone.
[0007] The disadvantages of polytetrafluoroethylene, such as poor mechanical properties and lack of obvious antibacterial properties, have always restricted its further application in the field of pharmaceutical packaging. The present invention modifies polytetrafluoroethylene by introducing modified cellulose-based polymers, silicon dioxide / sodium silicate composite materials, modified nano metal oxides and polyvinyl pyrrolidone: the modified nano metal oxides and modified cellulose-based polymers work synergistically to improve the toughness and hardness of the polytetrafluoroethylene composite material while giving the material a certain antibacterial and antibacterial effect, thereby helping to protect the safety of pharmaceutical products; the introduced silicon dioxide / sodium silicate composite material can enhance the wear resistance and heat resistance of polytetrafluoroethylene and improve its performance stability in harsh environments; at the same time, the combination of polyvinyl pyrrolidone and cellulose-based polymers can significantly improve the processing performance of polytetrafluoroethylene, enhance its molding fluidity and processing adaptability, and facilitate subsequent processing.
[0008] As a preferred technical solution of the present invention, the polytetrafluoroethylene composite material comprises the following components in parts by weight:
[0009] 80-90 parts of polytetrafluoroethylene;
[0010] 3-7 parts of modified cellulose-based polymer;
[0011] 2-5 parts of silicon dioxide / sodium silicate composite material;
[0012] 2-5 parts of modified nano metal oxide;
[0013] Polyvinyl pyrrolidone 1-3 parts.
[0014] Wherein, the mass parts of polytetrafluoroethylene can be 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts or 90 parts, the mass parts of modified cellulose-based polymer can be 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts or 7 parts, and the mass parts of silicon dioxide / sodium silicate composite material can be 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts or 5.0 parts, the mass parts of modified nano metal oxide can be 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts or 5.0 parts, and the mass parts of polyvinyl pyrrolidone can be 1.0 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3.0 parts, but are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0015] The introduced natural high molecular weight cellulose-based polymer can significantly improve the toughness of polytetrafluoroethylene, thereby enhancing its impact resistance. This is because the molecular structure of cellulose-based polymers can effectively disperse and absorb external impact energy, reducing the possibility of material breakage. At the same time, cellulose-based polymers have good biocompatibility and partial degradability, making this composite material have potential application prospects in the fields of medical devices and biomaterials. In addition, cellulose-based polymers are derived from nature and can be degraded in the environment, which is in line with the goal of sustainable development and reduces pollution to the environment. Modifying it with acetamide can increase the polar groups on its surface, enhance the biocompatibility of the material, and improve the mechanical strength of the cellulose-based polymer.
[0016] The present invention specifically limits the mass fraction of the modified cellulose-based polymer to 3-7 parts. When the addition amount of the cellulose-based polymer is too high, the composite material will become brittle, thereby reducing the impact resistance of the composite material; and a high content of cellulose-based polymer may affect the rheology and processing properties of the material, making it more difficult to process and shape.
[0017] The composite material provided by the present invention is added with modified nano metal oxide. Since the nano metal oxide particles have the advantages of high strength, high specific surface area and high surface energy, they form a larger contact area with the polymer matrix and generate more interactions, so the nano metal oxide particles can enhance the mechanical properties of the composite material. At the same time, zinc oxide or silver oxide has natural antibacterial and antibacterial properties, thereby giving the material a certain antibacterial and antibacterial effect. Modifying the nano metal oxide by chitosan can effectively improve its dispersibility and reduce particle agglomeration; chitosan can be combined with the surface of zinc oxide through hydrogen bonds or electrostatic effects, thereby enhancing the interface bonding strength of the composite material. In addition, chitosan itself has good biocompatibility and antibacterial properties, which also helps to further improve the comprehensive performance of the composite material.
[0018] The present invention specifically limits the mass fraction of the modified nano-metal oxide to 2-5 parts. When the amount of the nano-metal oxide added is too much, the excessively high content easily leads to particle agglomeration, reduces its dispersibility in the matrix, and affects the uniformity and mechanical properties of the composite material.
[0019] The addition of sodium silicate can enhance the mechanical properties and thermal stability of polytetrafluoroethylene composites and extend the service life of the material. Silicates have a unique layered structure and excellent chemical stability, which can improve the performance of materials under high temperature and friction conditions to a certain extent; and sodium silicate has a certain alkaline environment, which may help inhibit the growth of certain microorganisms and enhance the antibacterial properties of polytetrafluoroethylene composites. The surface modification of sodium silicate by lauric acid and polyvinyl alcohol can improve its interfacial compatibility with polytetrafluoroethylene. At the same time, the in-situ grown silica as an inorganic rigid filler can improve the mechanical properties and thermal stability of the composite material; as an inorganic barrier layer, silica can effectively reduce the gas and water vapor permeability of the composite material, which makes it have application potential in pharmaceutical packaging materials.
[0020] The preferred Shore hardness range of the composite material of the present invention is 50-60HD. The composite material in this hardness range can provide appropriate flexibility and strength, ensuring that the material has good formability and durability during the packaging process, and can effectively protect the drug from damage; when the hardness is too high, the composite material lacks flexibility and cannot effectively adapt to changes in the shape of the package, and when subjected to impact or pressure, the solution undergoes brittle fracture, which may cause damage to the package, thereby failing to protect the integrity of the drug.
[0021] The reason why the mass fraction of silicate is limited to 2-5 parts in the present invention is that too much silicate will make the composite material too hard, reducing its toughness and impact resistance; at the same time, high content of silicate is easy to agglomerate in the matrix, affecting the uniformity and comprehensive performance of the composite material.
[0022] The addition of polyvinyl pyrrolidone can significantly improve the dispersion stability of modified nano metal oxide / cellulose-based polymer in the matrix, and also promote the dispersibility of silica / silicate composite materials to a certain extent. At the same time, the combination of polyvinyl pyrrolidone and cellulose-based polymer can significantly improve the processing performance of the composite material. Polyvinyl pyrrolidone has good solubility and fluidity, making the material more fluid during processing.
[0023] There is also a synergistic effect between the various components added to the polytetrafluoroethylene composite material:
[0024] (1) Nano-metal oxides provide a large number of active sites due to their extremely high specific surface area, which can form strong interfacial bonds with the functional groups of cellulose-based polymers. This interfacial interaction helps to enhance the mechanical properties of the composite material and may give the material certain antibacterial properties, because nano-metal oxides can inhibit the growth of bacteria through their surface reactions. Cellulose-based polymers, as flexible matrices, can effectively alleviate the stress concentration problem that nano-metal oxides may cause in composite materials, thereby significantly improving the toughness and impact resistance of the composite material.
[0025] (2) The combination of cellulose-based polymers and silicates can significantly improve the wear resistance and heat resistance of composites, mainly due to the complementary structural and chemical properties of the two. Cellulose-based polymers provide flexibility and toughness, enabling them to effectively absorb and disperse energy when responding to mechanical stress, while silicates are known for their excellent hardness and heat resistance and can remain stable in high temperature and high wear environments. This combination of flexibility and hardness provides composites with better overall performance. In addition, silicates in composites may help to evenly disperse cellulose-based polymers and reduce aggregation in the material, thereby enhancing the overall stability and durability of the composite.
[0026] In a second aspect, the present invention provides a method for preparing a polytetrafluoroethylene composite material, the preparation method comprising:
[0027] S1: after mixing anhydrous ethanol and deionized water, sodium silicate is added to obtain a sodium silicate solution, lauric acid and polyvinyl alcohol are added to the sodium silicate solution, and the mixture is stirred to obtain a mixed solution A, the mixed solution A is added dropwise to anhydrous ethanol and stirred, and the precipitate is washed with anhydrous ethanol, filtered to obtain a sodium silicate precipitate, and dried to obtain a modified sodium silicate; deionized water and ammonia water are added to anhydrous ethanol to mix to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added to obtain a mixed solution D, the mixed solution D is stirred and filtered, and the obtained silicon dioxide / sodium silicate precipitate is washed and dried to obtain a silicon dioxide / sodium silicate composite material;
[0028] S2: Mixing acetic acid and deionized water to obtain an acetic acid solution, then adding chitosan, stirring to obtain a chitosan solution, adding nano-metal oxide to the chitosan solution, reacting at room temperature, filtering, washing the obtained nano-metal oxide precipitate, and drying to obtain a modified nano-metal oxide; adding a cellulose-based polymer to anhydrous ethanol and stirring to obtain a mixed solution E, stirring to obtain a swelling solution, adding acetamide to the swelling solution to obtain a modified cellulose-based polymer solution; then adding the modified nano-metal oxide to obtain a reaction solution F, stirring at a constant temperature, during which the pH of the reaction solution F is adjusted with ammonia water, and the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried to obtain a modified nano-metal oxide / cellulose-based polymer;
[0029] S3: Dispersing polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano metal oxide / cellulose-based polymer, and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically dispersing and stirring to obtain a spinning solution; injecting the spinning solution into a syringe for spinning, and collecting the electrospun fibers on a receiving plate; placing the electrospun fibers in a drying oven to dry, to obtain the polytetrafluoroethylene composite material.
[0030] As a preferred technical solution of the present invention, in step S1, the volume ratio of anhydrous ethanol to deionized water in the sodium silicate solution is (7-9):(1-3), for example, it can be 7:3, 8:2 or 9:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the mass ratio of lauric acid to sodium silicate is 1:(5-10), for example, it can be 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the mass ratio of polyvinyl alcohol to sodium silicate is 1:(10~15), for example, it can be 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5 or 1:15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the dripping rate of the mixed solution A is 3~5mL / min, for example, it can be 3mL / min, 3.2mL / min, 3.4mL / min, 3.6mL / min, 3.8mL / min, 4mL / min, 4.2mL / min, 4.4mL / min, 4.6mL / min, 4.8mL / min or 5mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the drying temperature of the sodium silicate precipitation is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the drying time of the sodium silicate precipitation is 6 to 8 hours, for example, it can be 6 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours, 7 hours, 7.2 hours, 7.4 hours, 7.6 hours, 7.8 hours or 8 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the concentration of deionized water in anhydrous ethanol in the mixed solution B is 12-18 mol / L, for example, it can be 12 mol / L, 12.6 mol / L, 13.2 mol / L, 13.8 mol / L, 14.4 mol / L, 15 mol / L, 15.6 mol / L, 16.2 mol / L, 16.8 mol / L, 17.4 mol / L or 18 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the concentration of aqueous ammonia in anhydrous ethanol in the mixed solution B is 0.2~0.6mol / L, for example, it can be 0.2mol / L, 0.24mol / L, 0.28mol / L, 0.32mol / L, 0.36mol / L, 0.4mol / L, 0.44mol / L, 0.48mol / L, 0.52mol / L, 0.56mol / L or 0.6mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the concentration of ethyl orthosilicate in the mixed solution C is 2.4mmol / L~4.8mmol / L, for example, it can be 2.4mmol / L, 2.6mmol / L, 2.8mmol / L, 3.0mmol / L, 3.2mmol / L, 3.4mmol / L, 3.6mmol / L, 3.8mmol / L, 4.0mmol / L, 4.2mmol / L, 4.4mmol / L, 4.6mmol / L or 4.8mmol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the mass ratio of the ethyl orthosilicate to the modified sodium silicate is (0.1~0.5):1, for example, it can be 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional embodiments, the stirring temperature of the mixed solution D is 25-35°C, for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the stirring time of the mixed solution D is 2 to 4 hours, for example, it can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional examples, the temperature for drying the silicon dioxide / sodium silicate precipitation is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the drying time of the silicon dioxide / sodium silicate precipitation is 6 to 8 hours, for example, it can be 6 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours, 7 hours, 7.2 hours, 7.4 hours, 7.6 hours, 7.8 hours or 8 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] As a preferred technical solution of the present invention, in step S2, the volume ratio of acetic acid to deionized water is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the amount of chitosan in the chitosan solution is 5-15 g / L, for example, it can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L or 15 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the mass ratio of the nano metal oxide to chitosan is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the reaction time is 1 to 2 hours, for example, it can be 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional embodiments, the temperature for drying the nano metal oxide precipitation is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional examples, the drying time of the nano metal oxide precipitation is 4 to 6 hours, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h, 5.8h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional examples, the feeding amount of the cellulose-based polymer in the swelling solution is 10-30 g / L, for example, it can be 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L, 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the stirring temperature of the mixed solution E to obtain the swelling solution is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the stirring time of the mixed solution E to obtain the swelling solution is 1 to 2 hours, for example, 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the feeding amount of acetamide is 20-30 mL, for example, it can be 20 mL, 21 mL, 22 mL, 23 mL, 24 mL, 25 mL, 26 mL, 27 mL, 28 mL, 29 mL or 30 mL, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the dropping speed of acetamide is 5-6 mL / min, for example, it can be 5 mL / min, 5.1 mL / min, 5.2 mL / min, 5.3 mL / min, 5.4 mL / min, 5.5 mL / min, 5.6 mL / min, 5.7 mL / min, 5.8 mL / min, 5.9 mL / min or 6 mL / min, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the reaction temperature of the reaction solution F is 75~85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the reaction time of the reaction solution F is 4 to 6 hours, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h, 5.8h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional embodiments, the pH control range of the reaction solution F is 7 to 9, for example, it can be 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8 or 9, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional embodiments, the drying temperature of the composite precipitation is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the drying time of the composite precipitation is 8 to 12 hours, for example, it can be 8 hours, 8.4 hours, 8.8 hours, 9.2 hours, 9.6 hours, 10 hours, 10.4 hours, 10.8 hours, 11.2 hours, 11.6 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] As a preferred technical solution of the present invention, in step S3, the time for ultrasonic treatment of the spinning solution precursor is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the power of the ultrasonic treatment of the spinning liquid precursor is 200~300 W, for example, it can be 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the stirring time of the spinning liquid precursor is 1 to 2 hours, for example, it can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the spinning distance of the electrospinning device is 15 to 20 cm, for example, it can be 15 cm, 16 cm, 17 cm, 18 cm, 19 cm or 20 cm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the injection speed of the electrospinning equipment is 0.5~1.5mL / h, for example, it can be 0.5mL / h, 0.6mL / h, 0.7mL / h, 0.8mL / h, 0.9mL / h, 1.0mL / h, 1.1mL / h, 1.2mL / h, 1.3mL / h, 1.4mL / h, 1.5mL / h, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional instances, the spinning voltage of the electrospinning device is 15~20kV, for example, it can be 15kV, 15.5kV, 16kV, 16.5kV, 17kV, 17.5kV, 18kV, 18.5kV, 19kV, 19.5kV or 20kV, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional instances, the temperature at which the electrospun fibers are dried in a drying oven is 60-80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional examples, the electrospun fiber is placed in a drying oven for 12 to 24 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] The invention modifies polytetrafluoroethylene by introducing modified cellulose-based polymer, silicon dioxide / sodium silicate composite material, modified nano metal oxide and polyvinyl pyrrolidone: the modified nano metal oxide and the modified cellulose-based polymer work synergistically, and can improve the toughness and hardness of the polytetrafluoroethylene composite material while giving the material a certain antibacterial and antimicrobial effect, thereby helping to protect the safety of medical products; the introduced silicon dioxide / sodium silicate composite material can enhance the wear resistance and heat resistance of polytetrafluoroethylene, and improve its performance stability in harsh environments; meanwhile, the combination of polyvinyl pyrrolidone and cellulose-based polymer can significantly improve the processing performance of polytetrafluoroethylene, enhance its molding fluidity and processing adaptability, and facilitate subsequent processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 A flow chart of a method for preparing a polytetrafluoroethylene composite material for medical packaging provided in Examples 1-4 of the present invention;
[0071] Figure 2 This is a scanning electron microscope image of the electrospun fiber provided in Example 1 of the present invention;
[0072] Figure 3 This is a transmission electron microscope image of the electrospun fiber provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0074] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:
[0075] Anhydrous ethanol: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0076] Sodium silicate: purchased from Hubei Chengfeng Chemical Co., Ltd.;
[0077] Lauric acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0078] Polyvinyl alcohol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0079] Ammonia water: purity 25%, purchased from Shandong Zhongyuan Chemical Co., Ltd.;
[0080] Tetraethyl orthosilicate: purchased from Shanghai Zhuorui Chemical Co., Ltd.
[0081] Acetic acid: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0082] Chitosan: purchased from Xi'an Kangnuo Chemical Co., Ltd.
[0083] Nano zinc oxide: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0084] Nano silver oxide: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0085] Hydroxyethyl cellulose: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0086] Carboxymethyl cellulose: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0087] Acetamide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0088] Polytetrafluoroethylene: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0089] Polyvinyl pyrrolidone: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0090] Example 1
[0091] This embodiment provides a polytetrafluoroethylene composite material for medical packaging and a preparation method thereof, wherein the composite material comprises the following components in parts by weight:
[0092] 86 parts of polytetrafluoroethylene
[0093] Modified hydroxyethyl cellulose 5 parts
[0094] 4 parts of modified nano zinc oxide
[0095] 3 parts of silicon dioxide / sodium silicate composite material
[0096] 2 parts of polyvinyl pyrrolidone
[0097] like Figure 1 As shown, the preparation method specifically comprises the following steps:
[0098] S1: Anhydrous ethanol and deionized water are mixed in a volume ratio of 9:1, and sodium silicate is added to obtain a sodium silicate solution. Lauric acid and polyvinyl alcohol are added to the sodium silicate solution, wherein the mass ratio of lauric acid to sodium silicate is 1:8, and the mass ratio of polyvinyl alcohol to sodium silicate is 1:13. The mixed solution A is stirred to obtain a mixed solution A. The mixed solution A is added dropwise to anhydrous ethanol at a dropping speed of 3.2 mL / L and stirred. The precipitate is washed with anhydrous ethanol and filtered to obtain a sodium silicate precipitate. The precipitate is dried at 75°C for 6.6 h to obtain a modified sodium silicate. Deionized water and aqueous ammonia are added to the anhydrous ethanol and mixed. The mixture is mixed, wherein the concentration of deionized water is 13 mol / L and the concentration of ammonia water is 0.5 mol / L, to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C, wherein the concentration of tetraethyl orthosilicate is 3.2 mmol / L; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added, and the mass ratio of tetraethyl orthosilicate to sodium silicate is 0.3:1, and the obtained mixed solution D is stirred at 28°C for 2h, filtered, and a silicon dioxide / sodium silicate precipitate is obtained, which is washed and dried at 50°C for 8h to obtain a silicon dioxide / sodium silicate composite material;
[0099] S2: Acetic acid and deionized water are mixed in a volume ratio of 1:10 to obtain an acetic acid solution, and chitosan is subsequently added, wherein the amount of chitosan is 10 g / L, and the chitosan solution is obtained by stirring, and nano zinc oxide is added to the chitosan solution, wherein the mass ratio of nano zinc oxide to chitosan is 1:12, and the reaction is carried out at room temperature for 1.5 hours, filtered, and the obtained nano metal oxide precipitate is washed and dried at 56°C for 5.5 hours to obtain modified nano zinc oxide; hydroxyethyl cellulose is added in an amount of 12 g / L. L is added to anhydrous ethanol to obtain a mixed solution E, and the mixed solution E is stirred at 70°C for 1.2 hours to obtain a swelling solution, and acetamide is added dropwise to the swelling solution, with the feeding amount of acetamide being 20mL / L and the dropping speed being 5mL / min to obtain a modified hydroxyethyl cellulose solution; then the modified nano zinc oxide is added to obtain a reaction solution F, and the mixture is stirred at a constant temperature of 80°C for 5 hours, during which the pH of the reaction solution F is adjusted to 8 with ammonia water, and the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried at 60°C for 12 hours to obtain a modified nano zinc oxide / hydroxyethyl cellulose;
[0100] S3: Disperse polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano zinc oxide / hydroxyethyl cellulose and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically disperse the solution, wherein the ultrasonic treatment time is 20 min, the ultrasonic treatment power is 300 W, and the spinning solution is obtained by stirring for 1 h; inject the spinning solution into a syringe for spinning, wherein the spinning distance of the electrospinning equipment is 15 cm, the injection speed of the spinning solution is 0.8 mL / h, and the spinning voltage is 18 kV, and the SEM image of the electrospun fiber is collected on the receiving plate as shown in FIG. Figure 2As shown in the TEM image Figure 3 As shown; the electrospun fiber is placed in an oven at a constant temperature of 60° C. and dried for 24 hours to obtain the polytetrafluoroethylene composite material.
[0101] Example 2
[0102] This embodiment provides a polytetrafluoroethylene composite material for medical packaging and a preparation method thereof, wherein the composite material comprises the following components in parts by weight:
[0103] 80 parts of polytetrafluoroethylene
[0104] 4 parts of modified hydroxyethyl cellulose
[0105] 5 parts of modified nano silver oxide
[0106] 5 parts of silicon dioxide / sodium silicate composite material
[0107] Polyvinyl pyrrolidone 1 part
[0108] like Figure 1 As shown, the preparation method specifically comprises the following steps:
[0109] S1: Anhydrous ethanol and deionized water are mixed in a volume ratio of 7:3, and sodium silicate is added to obtain a sodium silicate solution. Lauric acid and polyvinyl alcohol are added to the sodium silicate solution, wherein the mass ratio of lauric acid to sodium silicate is 1:9, and the mass ratio of polyvinyl alcohol to sodium silicate is 1:10. The mixed solution A is stirred to obtain a mixed solution A. The mixed solution A is added dropwise to anhydrous ethanol at a dropping speed of 5 mL / L and stirred. The precipitated precipitate is washed with anhydrous ethanol and filtered to obtain a sodium silicate precipitate. The precipitate is dried at 72°C for 7 hours to obtain a modified sodium silicate. Deionized water and ammonia water are added to the anhydrous ethanol and mixed. The concentration of deionized water is 12 mol / L, and the concentration of ammonia water is 0.2 mol / L, to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C, wherein the concentration of tetraethyl orthosilicate is 2.4 mmol / L; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added, and the mass ratio of tetraethyl orthosilicate to sodium silicate is 0.1:1, and the obtained mixed solution D is stirred at 35°C for 3h, filtered, and a silicon dioxide / sodium silicate precipitate is obtained, which is washed and dried at 52°C for 6h to obtain a silicon dioxide / sodium silicate composite material;
[0110] S2: Acetic acid and deionized water are mixed in a volume ratio of 1:15 to obtain an acetic acid solution, chitosan is subsequently added in an amount of 8 g / L, and the chitosan solution is obtained by stirring, and nano silver oxide is added to the chitosan solution, wherein the mass ratio of nano silver oxide to chitosan is 1:10, the reaction is carried out at room temperature for 1 hour, filtered, and the obtained nano metal oxide precipitate is washed and dried at 60°C for 6 hours to obtain modified nano silver oxide; hydroxyethyl cellulose is added in an amount of 25 g / L L is added to anhydrous ethanol to obtain a mixed solution E, the mixed solution E is stirred at 72°C for 1 hour to obtain a swelling solution, acetamide is added dropwise to the swelling solution, the feeding amount of acetamide is 22mL / L, and the dropping speed is 6mL / min to obtain a modified hydroxyethyl cellulose solution; then the modified nano silver oxide is added to obtain a reaction solution F, and the mixture is stirred at a constant temperature of 75°C for 6 hours, during which the pH of the reaction solution F is adjusted to 9 with ammonia water, and the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried at 65°C for 10 hours to obtain a modified nano silver oxide / hydroxyethyl cellulose;
[0111] S3: Disperse polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano silver oxide / hydroxyethyl cellulose and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically disperse the solution, wherein the ultrasonic treatment time is 28 min, the ultrasonic treatment power is 200 W, and the spinning solution is stirred for 1.8 h to obtain the spinning solution; inject the spinning solution into a syringe for spinning, wherein the spinning distance of the electrospinning equipment is 18 cm, the injection speed of the spinning solution is 0.5 mL / h, and the spinning voltage is 20 kV, and the electrospun fibers are collected on a receiving plate; the electrospun fibers are placed in an oven at a constant temperature of 64°C and dried for 20 h to obtain the polytetrafluoroethylene composite material.
[0112] Example 3
[0113] This embodiment provides a polytetrafluoroethylene composite material for medical packaging and a preparation method thereof, wherein the composite material comprises the following components in parts by weight:
[0114] 90 parts of polytetrafluoroethylene
[0115] 3 parts of modified carboxymethyl cellulose
[0116] 2 parts of modified nano silver oxide
[0117] 2 parts of silicon dioxide / sodium silicate composite material
[0118] Polyvinyl pyrrolidone 1 part
[0119] like Figure 1 As shown, the preparation method specifically comprises the following steps:
[0120] S1: Anhydrous ethanol and deionized water are mixed in a volume ratio of 8:2, and sodium silicate is added to obtain a sodium silicate solution. Lauric acid and polyvinyl alcohol are added to the sodium silicate solution, wherein the mass ratio of lauric acid to sodium silicate is 1:10, and the mass ratio of polyvinyl alcohol to sodium silicate is 1:15. The mixed solution A is stirred to obtain a mixed solution A. The mixed solution A is added dropwise to anhydrous ethanol at a dropping speed of 3 mL / L and stirred. The precipitated precipitate is washed with anhydrous ethanol and filtered to obtain a sodium silicate precipitate. The precipitate is dried at 60° C. for 8 h to obtain a modified sodium silicate. Deionized water and ammonia water are added to the anhydrous ethanol and mixed. The concentration of deionized water is 17 mol / L, and the concentration of ammonia water is 0.4 mol / L, to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C, wherein the concentration of tetraethyl orthosilicate is 4.8 mmol / L; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added, and the mass ratio of tetraethyl orthosilicate to sodium silicate is 0.5:1, and the obtained mixed solution D is stirred at 25°C for 3.5 hours, filtered, and a silicon dioxide / sodium silicate precipitate is obtained, which is washed and dried at 60°C for 7 hours to obtain a silicon dioxide / sodium silicate composite material;
[0121] S2: Acetic acid and deionized water are mixed in a volume ratio of 1:12 to obtain an acetic acid solution, chitosan is subsequently added in an amount of 15 g / L, and the chitosan solution is obtained by stirring, nano silver oxide is added to the chitosan solution, wherein the mass ratio of nano silver oxide to chitosan is 1:20, the reaction is carried out at room temperature for 2 h, filtered, the obtained nano metal oxide precipitate is washed and dried at 50°C for 4 h to obtain modified nano silver oxide; carboxymethyl cellulose is added in an amount of 10 g / L to obtain a modified nano silver oxide. L is added to anhydrous ethanol to obtain a mixed solution E, the mixed solution E is stirred at 78°C for 1.8 hours to obtain a swelling solution, acetamide is added dropwise to the swelling solution, the feeding amount of acetamide is 28mL / L, and the dropping speed is 5.2mL / min to obtain a modified carboxymethyl cellulose solution; then the modified nano silver oxide is added to obtain a reaction solution F, which is stirred at a constant temperature of 85°C for 4 hours, during which the pH of the reaction solution F is regulated to 7 with ammonia water, the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried at 78°C for 8 hours to obtain a modified nano silver oxide / carboxymethyl cellulose;
[0122] S3: Disperse polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano silver oxide / carboxymethyl cellulose and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically disperse the solution, wherein the ultrasonic treatment time is 21 min, the ultrasonic treatment power is 280 W, and the spinning solution is stirred for 1.4 h to obtain the spinning solution; inject the spinning solution into a syringe for spinning, wherein the spinning distance of the electrospinning equipment is 16 cm, the injection speed of the spinning solution is 1.1 mL / h, and the spinning voltage is 15 kV, and the electrospun fibers are collected on a receiving plate; the electrospun fibers are placed in an oven at a constant temperature of 75°C and dried for 18 h to obtain the polytetrafluoroethylene composite material.
[0123] Example 4
[0124] This embodiment provides a polytetrafluoroethylene composite material for medical packaging and a preparation method thereof, wherein the composite material comprises the following components in parts by weight:
[0125] 82 parts of polytetrafluoroethylene
[0126] 6 parts of modified carboxymethyl cellulose
[0127] 4 parts of modified nano zinc oxide
[0128] 5 parts of silicon dioxide / sodium silicate composite material
[0129] 3 parts of polyvinyl pyrrolidone
[0130] like Figure 1 As shown, the preparation method specifically comprises the following steps:
[0131] S1: Anhydrous ethanol and deionized water are mixed in a volume ratio of 8:2, and sodium silicate is added to obtain a sodium silicate solution. Lauric acid and polyvinyl alcohol are added to the sodium silicate solution, wherein the mass ratio of lauric acid to sodium silicate is 1:5, and the mass ratio of polyvinyl alcohol to sodium silicate is 1:11. The mixed solution A is stirred to obtain a mixed solution A. The mixed solution A is added dropwise to anhydrous ethanol at a dropping speed of 4.5 mL / L and stirred. The precipitated precipitate is washed with anhydrous ethanol and filtered to obtain a sodium silicate precipitate, which is dried at 80°C for 6 h to obtain a modified sodium silicate. Deionized water and ammonia water are added to the anhydrous ethanol and mixed. The concentration of deionized water is 18 mol / L, and the concentration of ammonia water is 0.6 mol / L, to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C, wherein the concentration of tetraethyl orthosilicate is 3.8 mmol / L; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added, and the mass ratio of tetraethyl orthosilicate to sodium silicate is 0.2:1, and the obtained mixed solution D is stirred at 30°C for 4 hours, filtered, and a silicon dioxide / sodium silicate precipitate is obtained, which is washed and dried at 55°C for 6.5 hours to obtain a silicon dioxide / sodium silicate composite material;
[0132] S2: Acetic acid and deionized water are mixed in a volume ratio of 1:15 to obtain an acetic acid solution, and chitosan is subsequently added, wherein the amount of chitosan is 5 g / L, and the chitosan solution is obtained by stirring, and nano zinc oxide is added to the chitosan solution, wherein the mass ratio of nano zinc oxide to chitosan is 1:18, and the reaction is carried out at room temperature for 1.2 hours, filtered, and the obtained nano metal oxide precipitate is washed and dried at 52°C for 5 hours to obtain modified nano zinc oxide; carboxymethyl cellulose is added in an amount of 30 g / L. L is added to anhydrous ethanol to obtain a mixed solution E, the mixed solution E is stirred at 80°C for 2h to obtain a swelling solution, acetamide is added dropwise to the swelling solution, the feeding amount of acetamide is 30mL / L, and the dropping speed is 5.8mL / min to obtain a modified carboxymethyl cellulose solution; then the modified nano zinc oxide is added to obtain a reaction solution F, which is stirred at a constant temperature of 82°C for 5.6h, during which the pH of the reaction solution F is regulated to 8.4 with ammonia water, the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried at 80°C for 11h to obtain a modified nano zinc oxide / carboxymethyl cellulose;
[0133] S3: Disperse polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano zinc oxide / carboxymethyl cellulose and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically disperse the solution, wherein the ultrasonic treatment time is 30 min, the ultrasonic treatment power is 210 W, and the spinning solution is stirred for 2 h to obtain the spinning solution; inject the spinning solution into a syringe for spinning, wherein the spinning distance of the electrospinning equipment is 20 cm, the injection speed of the spinning solution is 1.5 mL / h, and the spinning voltage is 16 kV, and the electrospun fibers are collected on a receiving plate; the electrospun fibers are placed in an oven at a constant temperature of 80°C and dried for 12 h to obtain the polytetrafluoroethylene composite material.
[0134] Comparative Example 1
[0135] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of modified nano zinc oxide in the composite material is adjusted to 10 parts. Compared with Example 1, the mass fraction of modified nano zinc oxide in this embodiment is increased by 6 parts, and the increased 6 parts are deducted from the mass fractions of polytetrafluoroethylene, modified hydroxyethyl cellulose, silicon dioxide / sodium silicate composite material, and polyvinyl pyrrolidone in a middle proportion, so that the mass fraction ratios of other components except modified nano zinc oxide remain unchanged. The mass fractions of each component of the adjusted composite material are as follows:
[0136] 80.62 parts of polytetrafluoroethylene
[0137] Modified hydroxyethyl cellulose 4.69 parts
[0138] Modified nano zinc oxide 10 parts
[0139] 2.81 parts of silicon dioxide / sodium silicate composite material
[0140] 1.87 parts of polyvinyl pyrrolidone
[0141] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0142] Comparative Example 2
[0143] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of modified nano zinc oxide in the composite material is adjusted to 0.5 parts. Compared with Example 1, the mass fraction of modified nano zinc oxide in this embodiment is reduced by 1.5 parts, and the reduced 1.5 parts are added to the mass fractions of polytetrafluoroethylene, modified hydroxyethyl cellulose, silicon dioxide / sodium silicate composite material, and polyvinyl pyrrolidone in equal proportion, so that the mass fraction ratios of other components except modified nano zinc oxide remain unchanged. The mass fractions of each component of the adjusted composite material are as follows:
[0144] Polytetrafluoroethylene 87.34 parts
[0145] Modified hydroxyethyl cellulose 5.08 parts
[0146] 0.5 parts of modified nano zinc oxide
[0147] 3.05 parts of silicon dioxide / sodium silicate composite material
[0148] 2.03 parts of polyvinyl pyrrolidone
[0149] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0150] Comparative Example 3
[0151] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of modified hydroxyethyl cellulose in the composite material is adjusted to 12 parts. Compared with Example 1, the mass fraction of modified hydroxyethyl cellulose in this embodiment is increased by 7 parts, and the increased 7 parts are deducted from the mass fractions of polytetrafluoroethylene, modified nano zinc oxide, silicon dioxide / sodium silicate composite material, and polyvinyl pyrrolidone in a middle proportion, so that the mass fraction ratios of other components except modified hydroxyethyl cellulose remain unchanged. The mass fractions of each component of the adjusted composite material are as follows:
[0152] Polytetrafluoroethylene 79.66 parts
[0153] Modified hydroxyethyl cellulose 12 parts
[0154] 3.71 parts of modified nano zinc oxide
[0155] 2.78 parts of silicon dioxide / sodium silicate composite material
[0156] 1.85 parts of polyvinyl pyrrolidone
[0157] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0158] Comparative Example 4
[0159] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of modified hydroxyethyl cellulose in the composite material is adjusted to 1 part. Compared with Example 1, the mass fraction of modified hydroxyethyl cellulose in this embodiment is reduced by 4 parts, and the reduced 4 parts are added to the mass fractions of polytetrafluoroethylene, modified nano zinc oxide, silicon dioxide / sodium silicate composite material, and polyvinyl pyrrolidone in equal proportion, so that the mass fraction ratios of other components except modified hydroxyethyl cellulose remain unchanged. The mass fractions of each component of the composite material after adjustment are as follows:
[0160] Polytetrafluoroethylene 89.62 parts
[0161] 1 part modified hydroxyethyl cellulose
[0162] Modified nano zinc oxide 4.17 parts
[0163] 3.13 parts of silicon dioxide / sodium silicate composite material
[0164] 2.08 parts of polyvinyl pyrrolidone
[0165] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0166] Comparative Example 5
[0167] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of the silica / sodium silicate composite material in the composite material is adjusted to 6 parts. Compared with Example 1, the mass fraction of the silica / sodium silicate composite material in this embodiment is increased by 3 parts, and the increased 3 parts are deducted from the mass fractions of polytetrafluoroethylene, modified nano zinc oxide, modified hydroxyethyl cellulose, and polyvinyl pyrrolidone in a middle proportion, so that the mass fraction ratios of other components except the silica / sodium silicate composite material remain unchanged. The mass fractions of each component of the adjusted composite material are as follows:
[0168] Polytetrafluoroethylene 83.34 parts
[0169] Modified hydroxyethyl cellulose 4.85 parts
[0170] 3.88 parts of modified nano zinc oxide
[0171] 6 parts of silicon dioxide / sodium silicate composite material
[0172] 1.94 parts of polyvinyl pyrrolidone
[0173] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0174] Comparative Example 6
[0175] This embodiment provides a polytetrafluoroethylene composite material, which is different from Example 1 in that the mass fraction of the silica / sodium silicate composite material in the composite material is adjusted to 1 part. Compared with Example 1, the mass fraction of the silica / sodium silicate composite material in this embodiment is reduced by 2 parts, and the reduced 2 parts are added to the mass fractions of polytetrafluoroethylene, modified nano zinc oxide, modified hydroxyethyl cellulose, and polyvinyl pyrrolidone in equal proportion, so that the mass fraction ratios of the other components except the silica / sodium silicate composite material remain unchanged. The mass fractions of the components of the adjusted composite material are as follows:
[0176] Polytetrafluoroethylene 87.77 parts
[0177] Modified hydroxyethyl cellulose 5.10 parts
[0178] 4.08 parts of modified nano zinc oxide
[0179] 1 part of silicon dioxide / sodium silicate composite material
[0180] 2.04 parts of polyvinyl pyrrolidone
[0181] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0182] The performance test of the polytetrafluoroethylene composite materials of the above-mentioned Examples 1-4 and Comparative Examples 1-6 was carried out, and the specific process is as follows:
[0183] The morphology of the electrospun fibers in Example 1 was tested by scanning electron microscopy (SEM) and transmission electron microscopy (TEM);
[0184] The tensile properties of the composite material were tested using an electronic tensile tester. The size of the experimental specimen was cut to 5mm×50mm, the tensile speed was set to 0.5mm / s, and 5 specimens were selected for each sample for tensile testing;
[0185] According to the national standard GB / T 2411-2008 (ISO 868-2003), the Shore hardness test is carried out at room temperature using an HSD digital Shore hardness tester;
[0186] The antibacterial and antibacterial effect test was carried out according to the antibacterial performance test method of non-dissolving antibacterial (inhibitory) products in Appendix C5 of the national standard GB / T 15979-2002;
[0187] All test results are shown in Table 1:
[0188] Table 1: Performance test results of polytetrafluoroethylene composite materials of Examples 1-4 and Comparative Examples 1-6
[0189]
[0190] It can be seen from the data in Table 1 that the polytetrafluoroethylene composite materials prepared in Examples 1-4 provided by the present invention have both good mechanical properties and excellent antibacterial and antimicrobial effects, which is very conducive to its wide application in the fields of medical devices, drug containers, and pharmaceutical packaging.
[0191] It can be seen from the test results of Example 1, Comparative Example 1 and Comparative Example 2 that when the mass fraction of nano-metal oxide in the composite material is in the range of 2-5 parts, since the nano-metal oxide particles have the advantages of high particle strength, high specific surface area and high surface energy, they can produce more interactions with the polymer matrix, so not only can the inherent properties of the matrix material be retained, but zinc oxide also has natural antibacterial and antibacterial properties, thereby giving the material a certain antibacterial and antibacterial effect; however, when the amount of nano-metal oxide added is too much, the excessively high content easily leads to particle agglomeration, reduces its dispersibility in the matrix, and affects the uniformity and related properties of the composite material.
[0192] It can be seen from the test results of Example 1, Comparative Example 3 and Comparative Example 4 that when the mass fraction of the cellulose-based polymer in the composite material is in the range of 3-7 parts, because the molecular structure of the cellulose-based polymer can effectively disperse and absorb external impact energy and reduce the possibility of material breakage, the introduced natural high molecular cellulose-based polymer can significantly improve the toughness and hardness of polytetrafluoroethylene, thereby enhancing its impact resistance; however, when the amount of cellulose-based polymer added is too much, it will cause the composite material to become brittle, thereby reducing the impact resistance of the composite material; and a high content of cellulose-based polymer may affect the rheology and processing properties of the material, making it more difficult to process and shape.
[0193] It can be seen from the test results of Example 1, Comparative Example 5 and Comparative Example 6 that when the mass fraction of silicate in the composite material is within the range of 2-5 parts, the silicate can react with polytetrafluoroethylene at the interface to form a stable siloxane bond on its surface. The formation of such siloxane bonds greatly improves the surface activity and affinity of polytetrafluoroethylene, enabling it to better combine with other fillers (such as nano metal oxides). Due to the introduction of silicate, the interfacial bonding force of the polytetrafluoroethylene composite material is significantly enhanced, which helps to improve the overall mechanical properties and service life of the material; however, when the amount of silicate added is too much, the excessive amount of silicate will make the composite material too hard, reducing its toughness and impact resistance; at the same time, high-content silicate is easy to agglomerate in the matrix, affecting the uniformity and comprehensive performance of the composite material.
[0194] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a polytetrafluoroethylene composite material for pharmaceutical packaging, characterized in that: The preparation method is: S1: after mixing anhydrous ethanol and deionized water, sodium silicate is added to obtain a sodium silicate solution, lauric acid and polyvinyl alcohol are added to the sodium silicate solution, and the mixture is stirred to obtain a mixed solution A, the mixed solution A is added dropwise to anhydrous ethanol and stirred, and the precipitate is washed with anhydrous ethanol, filtered to obtain a sodium silicate precipitate, and dried to obtain a modified sodium silicate; deionized water and ammonia water are added to anhydrous ethanol to mix to obtain a mixed solution B; tetraethyl orthosilicate is mixed with anhydrous ethanol to obtain a mixed solution C; the mixed solution B is mixed with the mixed solution C, and modified sodium silicate is added to obtain a mixed solution D, the mixed solution D is stirred and filtered, and the obtained silicon dioxide / sodium silicate precipitate is washed and dried to obtain a silicon dioxide / sodium silicate composite material; S2: Mixing acetic acid and deionized water to obtain an acetic acid solution, then adding chitosan, stirring to obtain a chitosan solution, adding nano-metal oxide to the chitosan solution, reacting at room temperature, filtering, washing the obtained nano-metal oxide precipitate, and drying to obtain a modified nano-metal oxide; adding a cellulose-based polymer to anhydrous ethanol to obtain a mixed solution E, stirring to obtain a swelling solution, adding acetamide to the swelling solution to obtain a modified cellulose-based polymer solution; then adding the modified nano-metal oxide to obtain a reaction solution F, stirring at a constant temperature, during which the pH of the reaction solution F is adjusted with ammonia water, and the obtained reaction solution G is cooled, filtered, and washed to obtain a complex precipitate, which is dried to obtain a modified nano-metal oxide / cellulose-based polymer; S3: dispersing polytetrafluoroethylene, silicon dioxide / sodium silicate composite material, modified nano metal oxide / cellulose-based polymer, and polyvinyl pyrrolidone into anhydrous ethanol solution to obtain a spinning solution precursor, and ultrasonically dispersing and stirring to obtain a spinning solution; injecting the spinning solution into a syringe for spinning, and collecting electrospun fibers on a receiving plate; placing the electrospun fibers in a drying oven to dry, to obtain the polytetrafluoroethylene composite material; The polytetrafluoroethylene composite material comprises the following components in parts by weight: 80-90 parts of polytetrafluoroethylene; 3-7 parts of modified cellulose-based polymer; 2-5 parts of silicon dioxide / sodium silicate composite material; 2-5 parts of modified nano metal oxide; and 1-3 parts of polyvinyl pyrrolidone.
2. The method for preparing the polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In step S1, The volume ratio of anhydrous ethanol to deionized water in the sodium silicate solution is (7-9): (3-1); The mass ratio of lauric acid to sodium silicate is 1:(5-10); The mass ratio of polyvinyl alcohol to sodium silicate is 1:(10-15); The mixed solution A is added dropwise at a rate of 3-5 mL / min; The temperature of the sodium silicate precipitation drying is 60-80°C; The drying time of the sodium silicate precipitation is 6 to 8 hours.
3. The method for preparing the polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In step S1, The concentration of deionized water in anhydrous ethanol in the mixed solution B is 12-18 mol / L; The concentration of ammonia water in anhydrous ethanol in the mixed solution B is 0.2-0.6 mol / L; The concentration of ethyl orthosilicate in the mixed solution C is 2.4 mmol / L to 4.8 mmol / L; The mass ratio of the tetraethyl orthosilicate to the modified sodium silicate is (0.1-0.5):1; The stirring temperature of the mixed solution D is 25-35°C; The stirring time of the mixed solution D is 2 to 4 hours; The temperature of the silicon dioxide / sodium silicate precipitation drying is 50-60°C; The drying time of the silicon dioxide / sodium silicate precipitation is 6 to 8 hours.
4. The method for preparing the polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In step S2, The volume ratio of the acetic acid to deionized water is 1:(10-20); The amount of chitosan in the chitosan solution is 5-15 g / L; The mass ratio of the nano metal oxide to chitosan is 1:(10-20); The reaction time is 1 to 2 hours; The temperature for the precipitation and drying of the nano metal oxide is 50-60°C; The time for the nano metal oxide precipitation and drying is 4 to 6 hours.
5. The method for preparing the polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In the step S2, The amount of cellulose-based polymer in the swelling solution is 10-30 g / L; The temperature of stirring the mixed solution E to obtain the swelling solution is 70-80° C.; The stirring time of the mixed solution E to obtain the swelling solution is 1 to 2 hours; The feeding amount of the acetamide is 20-30 mL / L; The dropping speed of the acetamide is 5-6 mL / min.
6. The method for preparing the polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In the step S2, The reaction temperature of the reaction solution F is 75-85°C; The reaction time of the reaction solution F is 4 to 6 hours; The pH of the reaction solution F is controlled in the range of 7 to 9; The drying temperature of the composite precipitation is 60-80°C; The drying time of the composite precipitation is 8 to 12 hours.
7. The method for preparing a polytetrafluoroethylene composite material for pharmaceutical packaging according to claim 1, characterized in that: In the step S3, The time of ultrasonic treatment of the spinning solution precursor is 20 to 30 minutes; The power of the ultrasonic treatment of the spinning solution precursor is 200-300W; The stirring time of the spinning solution precursor is 1 to 2 hours; The spinning distance of the electrospinning device is 15-20 cm; The spinning solution injection speed is 0.5-1.5 mL / h; The spinning voltage of the electrospinning is 15-20 kV; The electrospun fiber is placed in a drying oven and dried at a temperature of 60-80°C; The electrospun fibers are placed in a drying oven for drying for 12 to 24 hours.
8. A polytetrafluoroethylene composite material for pharmaceutical packaging prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The polytetrafluoroethylene composite material comprises the following components in parts by weight: 80-90 parts of polytetrafluoroethylene; 3-7 parts of modified cellulose-based polymer; 2-5 parts of silicon dioxide / sodium silicate composite material; 2-5 parts of modified nano metal oxide; Polyvinyl pyrrolidone 1-3 parts.
9. The polytetrafluoroethylene composite material for medical packaging according to claim 8, characterized in that: The cellulose-based polymer in the modified cellulose-based polymer is hydroxyethyl cellulose and / or carboxymethyl cellulose.
10. The polytetrafluoroethylene composite material for medical packaging according to claim 8, characterized in that: The nano metal oxide in the modified nano metal oxide is zinc oxide nano particles and / or silver oxide nano particles.
Citation Information
Patent Citations
Polytetrafluoroethylene composite material and product preparation method thereof
CN101775186B
Teflon composite material and preparation method thereof
CN102924854A
Multifunctional polyvinyl alcohol nano composite material and preparation method thereof
CN113801417A
Preparation method of polytetrafluoroethylene nanofiber membrane
CN116575184A